2004
DOI: 10.1097/00045391-200405000-00009
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effects of Herbal Components on CYP2C9 and CYP3A4 Catalytic Activities in Human Liver Microsomes

Abstract: Herbal medicines are widely consumed by patients in different clinical settings in the United States and all over the world. In this study, 7 herbal components ginsenosides Rb1, Rb2, Rc, and Rd (from ginseng quercetin) ginkgolides A and B (from ginkgo biloba) were investigated for their inhibitory effects on hepatic CYP2C9 and CYP3A4 catalytic activities in human liver microsomes. Tolbutamide 4-methylhydroxylation and testosterone 6beta-hydroxylation were used as index reactions of CYP2C9 or CYP3A4 catalytic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 20 publications
3
47
1
Order By: Relevance
“…Hence for each group. [60] and Numa et al, 2007 [61] proved that the active constituents of G. biloba have CYP2C9 inhibitory potential and the present results are in agreement with these reports. In contrast, our results are in contradictory to the results of Sugigyama et al, 2004 andUmegaki et al, 2002.…”
Section: Resultssupporting
confidence: 93%
“…Hence for each group. [60] and Numa et al, 2007 [61] proved that the active constituents of G. biloba have CYP2C9 inhibitory potential and the present results are in agreement with these reports. In contrast, our results are in contradictory to the results of Sugigyama et al, 2004 andUmegaki et al, 2002.…”
Section: Resultssupporting
confidence: 93%
“…The incidence of potential cytochrome P450 (P450)-mediated drug inhibition from herbal therapies has been noted for popular remedies such as St. John's wort, echinacea, ginseng, garlic, and saw palmetto (Obach, 2000;Foster et al, 2001;Chang et al, 2002;He and Edeki, 2004;Yale and Glurich, 2005;Liu et al, 2006;Modarai et al, 2007). Various herbal constituents have also been shown to induce P450 activity in vitro.…”
mentioning
confidence: 99%
“…For example, repetitive administration of St. John's wort decreases the blood concentrations of certain drugs, such as immunodepressants, by the induction of P450s (Piscitelli et al, 2000;Bauer et al, 2003). Some herbal extracts, such as ginkgo, echinacea, and soybean extracts, have been reported to inhibit P450s in vitro (He and Liu, 2002;Anderson et al, 2003;He and Edeki, 2004). We have reported that beverages such as green tea, which is processed into dietary supplements, inhibit the function of sulfotransferase (Nishimuta et al, 2005).…”
mentioning
confidence: 99%